Polymer Composites for Electrical and Electronic Engineering Application - He, Shaojian (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Polymer composite materials have attracted great interest for the development of electrical and electronic engineering and technology, and have been widely applied in electrical power systems, electrical insulation equipment, electrical and electronic devices, etc. Due to the significant expansion in the use of newly developed polymer composite materials, it is necessary to understand and accurately describe the relationship between composite structure and material properties, as only based on thorough laboratory characterization is it possible to estimate the properties for their future commercial applications. This book focuses on polymer composites applied in the field of electrical and electronic equipment, including but not limited to synthesis and preparation of new polymeric materials, structure-properties relationship of polymer composites, evaluation of materials application, simulation and modelling of material performance.